Penggunaan metode mind mapping terhadap kemampuan literasi siswa pada pembelajaran IPS - Arum Fatayan (ARKA INSTITUTE, 2022)
This research aims to determine whether or not there is an influence on students' literacy skills using the Mind Mapping method on class V students at SDN Pekayon 09 in semester 2 of the 2020–2021 academic year. This research uses quantitative methods. The type of research used is a quasi-experimental design with a posttest-only type and a non-equivalent control group design. The sampling technique used was the saturated-side technique. The sample studied was 60 students, consisting of 30 experimental class students and 30 control class students. The individual test research instrument is composed of 10 essay questions. From the test results, it was found that tcount was greater than ttable, so Ho was rejected and H1 was accepted. It can be concluded that there is quite a significant influence in the application of the mind mapping method on the literacy skills of class V students at SDN Pekayon 09. The mind mapping method has a positive impact and results in students becoming more active in asking and answering questions and more creative and innovative in their learning.